Manifestation of the Assael Model on Consumer Purchase Decisions with Modern Life Style as an Intervening Variable on Three International Fast-Food Brands in Soloraya - Sofia Anida Kusuma; Moechammad Nasir (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze and discuss the significant influence of brand awareness, brand association, and brand assets on lifestyle; the significant influence of brand awareness, brand association, and brand assets on brand loyalty; and the significant influence of brand awareness, brand association, and brand assets on brand loyalty mediated by lifestyle. The population in this study consists of all customers who have purchased international products, namely KFC and McDonald’s, as well as national products, namely Restoran Taman Sari and Dapur Solo in Surakarta, with a sample of 200 respondents. Data were collected through the distribution of questionnaires. The sampling technique used in this research was non-probability sampling with a purposive sampling method. Data analysis was conducted using Smart PLS 3, which included the outer model tests comprising convergent validity, discriminant validity, composite reliability, Cronbach’s alpha, and multicollinearity tests and the inner model tests comprising coefficient of determination, goodness of fit, effect size (f²) test, and hypothesis testing. The results of this study indicate that brand loyalty toward fast-food restaurants in Surakarta is significantly influenced by brand awareness, brand association, and brand assets, with lifestyle serving as a moderating variable that strengthens this relationship. These findings support the idea that shifts in contemporary lifestyles have an increasing impact on fast food consumption patterns. Practically, the results provide insights for fast-food restaurant operators on how to better tailor their marketing strategies to align with the lifestyle patterns of consumers.